The Effects Of Solar Irradiance, Reflecting Material And Intercept Factor To The Solar Power Intercepted By Receiver 1kw Parabolic Dish - Affandi, Rosnani; Liaw , Geok Pheng; Ab Ghani, Mohd Ruddin; Gan, Chin Kim (Trans Tech Publications, 2015)
Parabolic Dish (PD) system is one of the Concentrating Solar Power (CSP) technologies that converts the thermal energy from solar irradiance into mechanical energy and then to electrical energy. The concentrator in PD system works by focusing the solar radiation onto the receiver located at the focal point. The solar power that produced from the concentration process is intercepted by the receiver and then used for the energy conversion process in PD system. This study is carried out to understand the effect of the intercept factor, reflecting material and the DNI to the solar power intercepted by the receiver in PD 1kW system. Meanwhile, Matlab Simulink was used in this study as the simulation tool. The study shows that the solar power intercepted by the receiver in 1kW PD system are strongly depending on the intercept factor, DNI of the locations and reflecting material used for the concentrator. Whereas, the results from this study are useful for a better understanding especially on the effects of the intercept factor, reflecting material and the DNI to the solar power intercepted by the receiver for 1kW PD system in different locations with different DNI level.